PENGENDALIAN PENCEMARAN DAN EROSI BIBIR PANTAI DENGAN PENANAMAN MANGROVE DI PANTAI TIRANG, KELURAHAN TUGUREJO, KECAMATAN TUGU, KOTA SEMARANG JAWA TENGAH - Purwanto Purwanto; Sunu Arsy Pratomo; Dedy Rusmiyanto; Dhanan Abimanto; Rafdi Ma’ruf Satria (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
The community service program for planting mangrove trees at Tirang Beach, Semarang aims to increase public awareness of the importance of mangrove ecosystems and improve coastal environmental conditions. This program will be implemented through mangrove tree planting activities and counseling regarding the benefits of mangrove ecosystems for the environment. The method that will be used in this program is data collection through surveys to determine the level of public awareness regarding the importance of mangrove ecosystems and coastal environmental conditions. Furthermore, mangrove tree planting activities will be carried out together with the local community, involving experts in the environmental and fisheries fields. In addition, counseling will be carried out regarding the benefits of mangrove ecosystems for the environment, including as a place for various types of fish and wild animals to live, as well as protecting the coast from abrasion. Through this program, it is hoped that people will become more aware of the importance of preserving mangrove ecosystems and protecting the coastal environment. The expected results of this program are increasing public awareness of the importance of protecting the coastal environment and mangrove ecosystems, as well as increasing the number of mangrove trees on Tirang Beach. This program is also expected to be an example for other communities to preserve the environment and encourage the creation of a healthier and more sustainable environment.